Cybersecurity and Privacy in Cyber Physical Systems - Maleh, Yassine, 1987- editor; Mohammad Shojafar editor; Ashraf Darwish editor; AbdelKrim Haqiq editor (Boca Raton : CRC Press, 2019)
Includes bibliographical and references